WORKSHOP ON THE MAKING OF TEA-BASED BURSTING BOBA AT SMA KRISTEN KARUNIA JAKARTA - Lucia Crysanthy Soedirga; Nuri Arum Anugrahati; Natania Natania; Maurelle Nolita; Christine Joannita Kurniawan (Jurnal Sinergitas PKM & CSR, 2023)
Tea is one of the beverages widely consumed due to its functional aspects, yet its applications remain limited primarily to brewing. Another product that has gained significant popularity among the community, especially school-age children, is bursting popping boba due to its explosive sensation in the mouth. Bursting popping boba is produced using the spherification technique, a molecular gastronomy component. It is commonly based on sugar or syrup solutions. One approach that can enhance tea product diversification is transforming it into bursting popping boba. However, tea-based bursting popping boba has yet to be widely recognized by the public, exceptionally high school students. Hence, there is a need for a workshop on the production of bursting popping boba. This workshop was held on November 4, 2022, at SMA Kristen Karunia Jakarta. The Community Service Program activity was successfully executed and received positive feedback from the high school students of SMA Kristen Karunia Jakarta, as indicated by the questionnaire results. Specifically, 97.5% of the participants found this activity beneficial and informative. In comparison, 92.5% expressed interest in participating in such activities again.